Modelagem Euler-Lagrange do processo de incrustação - Mazuroski, Marina Elizabeth (2021)
Scale in downhole equipment and completion systems can cause productivity issues, with limited oil output, equipment damage and safety issues. This work proposes a numerical model for simulating liquid-solid flow for the scaling formation process in a cylindrical duct, inspired by the experimental test Dynamic Tube Blocking (DTB), incorporating the effects of crystal growth and adhesion through User Defined Functions (UDF). The solution is obtained using an Euler-Lagrange approach, with the numerical formulation done by the CFD-DEM coupled method and a four-way interaction between phases. The results are presented for scenarios with and without adhesion and particle growth, with evaluation of the effects of fluid flow Qβ (2,5; 5,0; 10 mL/min), particle diameter dp (20; 30; 40 μm), particle-fluid specific mass ratio ρp/β (2,5; 4,5; 6,5) and ratio of the adhesive force to the weight of the particle χ (0; 25; 50; 75; 100 (x103)). The analysis is done based on the shape of the particle bed, the fluid velocity field and through the pressure response over time. It was verified that fluid flow and particle diameter change the flow regime and the particle bed, producing different effects on the adhesion and pressure response. Furthermore, it was noticed the increase of pressure with the adhesive force ratio χ, with the highest tested value resulting in a 16-fold pressure increase over the single-phase flow. The proposed model allowed the analysis of the influence of growth and adhesion on the interaction between phases, indicating the relevance of different properties in the scaling problem. The results emphasize the pertinence of a numerical model for the detailed study of predominant effects.